Effects of alpha-lactalbumin on emotional processing in healthy women. - Scrutton, H; Carbonnier, A; Cowen, P; Harmer, C (2007)
The synthesis of serotonin (5-HT) in the central nervous system is dependent on the availability to the brain of its precursor amino acid, tryptophan (TRP). Recent studies suggest that alpha-lactalbumin, a whey-derived protein with a relatively high TRP content, increases plasma TRP and produces endocrine and cognitive changes consistent with facilitation of brain 5-HT function. In the present study we assessed the biochemical and cognitive effects of alpha-lactalbumin (40 g) in 28 healthy female subjects in a parallel group, placebo-controlled design. Relative to a casein-derived control protein, alpha-lactalbumin increased plasma TRP and the ratio of TRP to neutral amino acids. However, there was no effect on salivary cortisol secretion or tasks of emotional processing shown previously to be sensitive to pharmacological manipulation of 5-HT in healthy volunteers. The results suggest that alpha-lactalbumin produces a relatively modest increase in TRP availability which may not be sufficient to produce the changes in emotional processing seen with administration of pure TRP in healthy subjects. Further studies in subjects more vulnerable to stress are needed to assess the potential therapeutic effects of alpha-lactalbumin in clinical populations.